2014
DOI: 10.1093/infdis/jiu141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Impacts Over 5 Years of Artemisinin-Based Combination Therapies on Plasmodium falciparum Polymorphisms That Modulate Drug Sensitivity in Ugandan Children

Abstract: NCT00527800.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
124
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(150 citation statements)
references
References 46 publications
18
124
8
Order By: Relevance
“…However, earlier studies from Burkina Faso showed that prior treatment with DP did not select for pfcrt and pfmdr1 polymorphisms associated with resistance to CQ and AQ (28). These results differ from those in a recent study in Uganda, in which therapy with DP selected in recurrent infections for pfmdr1 polymorphisms (86Y and 1246Y) also selected by AQ-containing regimens (29). The reasons for different results between Uganda and Burkina Faso and for differential effects of the different aminoquinolines in Burkina Faso are not known.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, earlier studies from Burkina Faso showed that prior treatment with DP did not select for pfcrt and pfmdr1 polymorphisms associated with resistance to CQ and AQ (28). These results differ from those in a recent study in Uganda, in which therapy with DP selected in recurrent infections for pfmdr1 polymorphisms (86Y and 1246Y) also selected by AQ-containing regimens (29). The reasons for different results between Uganda and Burkina Faso and for differential effects of the different aminoquinolines in Burkina Faso are not known.…”
Section: Discussioncontrasting
confidence: 84%
“…Specifically, in infections occurring within 28 to 42 days of prior therapy in Burkina Faso, AQ/SP selected for mutations in pfdhfr, pfdhps, pfcrt, and pfmdr1 associated with drug resistance, but DP did not select for any of these polymorphisms (20,26,28). However, in a recent study in East Africa, prior use of DP selected in recurrent infections for polymorphisms in pfmdr1 that were also selected for by AQ/SP (29); the reasons for differences in selection between East and West Africa are unknown. To evaluate the relative selective pressures of AQ/SP and DP administered as SMC, we evaluated the prevalences of key resistance-mediating P. falciparum polymorphisms in parasites collected from children before the initiation of the intervention, from children a month after the completion of three monthly treatments, and from a control group of children not subject to the intervention.…”
mentioning
confidence: 99%
“…This effect of C350R on QN and MQ, however, was not replicated in field isolates, underscoring a complex genetic basis of susceptibility in the field. Another primary determinant of susceptibility to these drugs in P. falciparum is the pfmdr1 gene, which in French Guiana harbors the 86N and 184F residues that are associated with increased LUM susceptibility (31,32). Of note, all isolates remained highly susceptible to LUM, a finding that argues for maintaining the artemether + LUM combination as first-line therapy in the region.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the A578S polymorphism is present in Africa (8,(24)(25)(26)(27)(28) and Bangladesh (29). Conflicting findings have been reported regarding the role of A578S in artemisinin resistance (8,26,30). Previous computational modeling using the betapropeller domain of the btbkelch protein krp1 (PDB ID 2WOZ) suggested that a structural change induced by the A578S mutation potentially disrupts the normal function of the Pfkelch13 protein (29).…”
Section: Discussionmentioning
confidence: 99%